Psychometric properties of the Iranian version of the dissociative experiences measure, Oxford (DEMO) - Seyed Ruhollah Hosseini; Sepehr Maghsoudi; Abbas Firoozabadi; Nikzad Ghanbari; Maryam Shamsaei (BMC Psychiatry)
Abstract Backgrounds Dissociative experiences are described as crucial psychological mechanisms involving the organism’s responses to severe psychological traumas and unpleasant past experiences. This research was conducted to examine the psychometric properties of the Dissociative Experiences Measure, Oxford (DEMO) in the Iranian general population. Methods This study used cross-sectional correlation, and the statistical population consisted of Iranians over 15 years old. Among them, 712 subjects were chosen as the study sample using the convenience sampling technique. Data were acquired between February and April 2022 using DEMO, Dissociative Experiences Scale II (DES-II), and Depression Anxiety and Stress Scale (DASS-21). In order to determine DEMO’s psychometric properties, Confirmatory Factor Analysis (CFA) was used to investigate the factorial structure, Cronbach’s alpha analyses to examine the internal consistency reliability, and Pearson correlation analyses to examine the relationships between DEMO’s subscales and the subscales of DES-II and DASS-21, indicating convergent validity. In order to analyze the data, LISREL 8.0 and SPSS-26 were used. Results Based on the results of the CFA, the proposed five-factor structure of DEMO showed an acceptable fit to the data (χ² = 1939.81, SRMR = 0.078, CFI = 0.96, RMSEA = 0.074). The internal reliability was satisfactory for the total scale (Cronbach’s alpha = 0.93) and the five subscales (Cronbach’s alpha = 0.89 for unreality, 0.87 for numb and disconnected, 0.80 for memory blanks, 0.85 for zoned out, and 0.79 for vivid internal world). The CFA results indicated that the five factors explained 60.69% of the variance. Significant correlations were observed between the DEMO subscales and the respective subscales of DES-II and DASS-21, confirming the measure’s convergent validity. Conclusion It can be concluded from the results of this study that the DEMO has high reliability and validity among the Iranian general population.